Swath sonar multibeam EM710 bathymetry during METEOR cruise M84/2 with links to raw data files of bathymetry from Georgia. - Wintersteller, Paul; dos Santos Ferreira, Christian (PANGAEA, 2018)
Multibeam echosounder (MBES) data recorded during RV METEOR cruise M84-2 between 26.02.2011 and 02.04.2011 in the Black Sea. The aim of the cruise was to investigate the gas hydrate distribution in sediments of the Black Sea by using several coring technics. In addition to the coring activities the installed EM122 and the PARASOUND system were used to detect gas emissions in the water column and to map large areas of possible seep sites. CI Citation: Paul Wintersteller & Christian dos Santos Ferreira (seafloor-imaging@marum.de) as responsible party for bathymetry and backscatter post-processing and its products. Description of the data source: During the RV METEOR cruise M84-2 the Kongsberg EM710 shallow multibeam echosounder with a nominal sounding frequency of 70-100 kHz was utilized. 256 beams (and up to 800 soundings in equidistant and dual swath mode) are formed for each ping with 1°(Tx)/1°(Rx) footprint while the seafloor is detected using amplitude and phase information for each beam sounding. For further information consult http://epic.awi.de/26726/1/Kon2007b.pdf . During M84-2 the EM710 was switched on only at shallower areas, with depths up to max. 1200 m. The swath coverage during bathymetric surveys was kept around 110-130° to avoid loss of data (due to system malfunctions) and data artefacts (like spikes and wobbling. The EM710 was run in dual swath mode. Responsible person during this cruise / PI: Paul Wintersteller (pwintersteller@marum.de) & Christian dos Santos Ferreira (cferreira@marum.de). Description of data processing: Postprocessing and products were conducted by the Seafloor-Imaging & Mapping group of MARUM/FB5, responsible person: Paul Wintersteller (seafloor-imaging@marum.de). The open source software MB-System suite (Caress, D.W., and D.N. Chayes, MB-System Version 5, open source software distributed from the MBARI and L-DEO web sites, 2000-2012.) was utilized for this purpose. A tide correction was applied, based on the Oregon State University (OSU) tidal prediction software (OTPS) that is retrievable through MB-System. In general, there is a tide difference of less than 20 cm in the Black Sea. Though CTD measurements were taken during the M84-2 cruise, these were not sufficient to represent the changes in sound velocity (SVP) throughout the study area, therefore a correction had to be applied. The corrections of the sound velocity is based on various SVP/CTD measurements throughout different cruises in the Black Sea within the last 15-20 years. In addition, the NATO Black Sea data base (http://sfp1.ims.metu.edu.tr/ODBMSDB/ODBMSDB.dll/querydb) was consulted for further CTD profiles in the given season/period of the year and in close position to the data set. The CTD data has then been used to calculate SVP by the usage of the UNESCO formula (G.S.K. Wong and S Zhu, Speed of sound in seawater as a function of salinity, temperature and pressure (1995) J. Acoust. Soc. Am. 97(3) pp 1732-1736). Changes in SVP and a slight draft offset correction (-5 m) have been applied (mbset). While further roll, pitch and heave corrections were not necessary for the M84-2 data. The bathymetric data was then cleaned for existing artefacts with mbeditviz. NetCDF (GMT) grids of the product and the statistics were created using mbgrid. No total propagated uncertainty (TPU) has been calculated to gather vertical or horizontal accuracy. The currently published bathymetric grid of the cruise has a resolution of 70 m. A higher resolution is, at least partly, achievable. The grid extended with _num represents a raster dataset with the statistical number of beams/depths taken into account to create the depth of the cell. The extended _sd -grid contains the standard deviation for each cell. All grids produced are retrievable through the PANGAEA database (www.pangaea.de). Chief Scientist: Gerhard Bohrmann (gbohrmann@marum.de) CR: http://doi.pangaea.de/10.2312/cr_m84_2 CSR: http://www.bsh.de/aktdat/dod/fahrtergebnis/2011/20110111.htm Publications related to the cruise: https://www.pangaea.de/search?ie=UTF-8&env=All&count=10&q=M84%2F2 GEORGIA Area Bathymetry EM710 published under https://doi.pangaea.de/10.1594/PANGAEA.839900 A special thanks goes to the watchkeeper during this cruise: E. Akarsu, J. Körber, S. Oelfke, A. Özmaral, V. Rădulescu, M. Römer, M. Schmager Another thanks goes to the student helper who helped to create this product: N. Brückner, S. Gaide, S. Oelfke
Gridded bathymetry from multibeam echosounder EM710 data of the cruise M84/2, off Georgia (2011)
Keywords: Black Sea; Center for Marine Environmental Sciences; CT; File format; File name; File size; M84/2; M84/2-track; MARUM; Meteor (1986); Underway cruise track measurements; Uniform resource locator/link to file